2008
DOI: 10.1128/jvi.02020-07
|View full text |Cite
|
Sign up to set email alerts
|

Early Phosphatidylinositol 3-Kinase/Akt Pathway Activation Limits Poliovirus-Induced JNK-Mediated Cell Death

Abstract: Poliovirus (PV)-induced apoptosis seems to play a major role in tissue injury in the central nervous system (CNS). We have previously shown that this process involves PV-induced Bax-dependent mitochondrial dysfunction mediated by early JNK activation in IMR5 neuroblastoma cells. We showed here that PV simultaneously activates the phosphatidylinositol 3-kinase (PI3K)/Akt survival signaling pathway in these cells, limiting the extent of JNK activation and thereby cell death. JNK inhibition is associated with PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 42 publications
2
45
0
1
Order By: Relevance
“…Individual treatment with these kinase inhibitors did not affect PV or EV71 infection, thus a synergy of these kinase inhibitors was essential for the inhibitory effect. This is consistent with a recent observation by Autret et al (2008) that PI3K/Akt signalling does not affect the growth of PV. In EMCV infection, wortmannin treatment even increased viral protein synthesis and the yield of virus (Svitkin et al, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…Individual treatment with these kinase inhibitors did not affect PV or EV71 infection, thus a synergy of these kinase inhibitors was essential for the inhibitory effect. This is consistent with a recent observation by Autret et al (2008) that PI3K/Akt signalling does not affect the growth of PV. In EMCV infection, wortmannin treatment even increased viral protein synthesis and the yield of virus (Svitkin et al, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…As previously reported by our group (Autret et al, 2007(Autret et al, , 2008Brisac et al, 2010) and by Agol's group (Agol et al, 2000;Belov et al, 2003), several series of events may be involved in the regulation of PV-induced apoptosis. The results presented here highlight a new pathway, the CREB/ Herp pathway, which plays an anti-apoptotic role.…”
Section: Herpmentioning
confidence: 56%
“…The induction of apoptosis during PV infection is controlled by a balance between survival pathways early in infection, allowing completion of the viral cycle, and the progression to programmed cell death later in infection (Agol et al, 2000;Autret et al, 2008;Belov et al, 2003). In this study, we showed that the CREB3/Herp signalling pathway was involved in modulating this balanced regulation.…”
Section: Herpmentioning
confidence: 70%
See 1 more Smart Citation
“…It has been reported that the PI3K pathway can negatively regulate JNK. 66 Thus inhibition of PI3K may result in activation of JNK.…”
Section: Discussionmentioning
confidence: 99%